Rhythmic Density Affects Listeners' Emotional Response to Microtiming - Senn, Olivier; Bullerjahn, Claudia; Kilchenmann, Lorenz; von Georgi, Richard (Frontiers in Psychology, 2017)
Microtiming has been assumed to be vital for the experience of groove, but past research presented conflicting results: some studies found that microtiming is irrelevant for groove, others reported that microtiming has a detrimental effect on the groove experience. The three studies in this paper aim at explaining some of these discrepancies by clarifying to what extent listeners’ emotional responses to microtiming depend on the distribution of microtiming deviations across instrumental parts (voicing) or other moderating factors like tempo or rhythmic density. The studies use data from two listening experiments involving expert bass and drums duo recordings in swing and funk style. – Study A investigates the effect of fixed time displacements within and between the parts played by different musicians. Listeners (n = 160) reacted negatively to irregularities within the drum track, but the mutual displacement of bass versus drums did not have an effect. – Study B develops three metrics to calculate the average microtiming magnitude in a musical excerpt. The experiment showed that listeners’ (n =160) emotional responses to expert performance microtiming aligned with each other across styles, when microtiming magnitude was adjusted for rhythmic density. This indicates that rhythmic density is a unifying moderator for listeners’ emotional response to microtiming in swing and funk. – Study C used the data from both experiments in order to compare the effect of fixed microtiming displacements (from Study A) with scaled versions of the originally performed microtiming patterns (from Study B). It showed that fixed snare drum displacements irritated expert listeners more than the more flexible deviations occurring in the original performances. This provides some evidence that listeners’ emotional response to microtiming deviations not only depends on the magnitude of the deviations, but also on the kind and origin of the microtiming patterns (fixed lab displacements vs. flexible performance microtiming).